(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Domestic violence is a wide spread problem, its actual extent is difficult to measure. According to available statistics throughout the world, about 33 percent women have experienced violence at some point of their life (WHO, 1997). In India, women form about half of the population and enjoy various freedom and rights but simultaneously, like other developing countries, violence against women is overwhelming and is a matter of concern. Domestic violence leads to violence of human rights and prevents them from enjoying their fundamental rights. Though the types of violence differs from society to society, nations to nations, religion to religion, but it prevails in underdeveloped, developing and developed countries, too. Domestic violence refers to “assaultive and coercive behaviours that adults use against their intimate partners” (Holden, 2003). In India, there are a set of well-equipped legislations which protect women against violence. And Protection of Women against Domestic Violence Act, 2005 is the milestone in the history of legal control and judicial response in domestic violence affairs. But the rate of violence against women increased 44 percent during 1993 to 2011. The findings of the paper are expected to enlighten individuals and the community on the causes and consequences of violence against women. The paper comes out with policy prescription for government and non-government organizations towards addressing the problem.